Analysis Of Village Fund Utilization For Community Empowerment In The Agricultural Sector: A Case Study Of Haruru Village, Amahai District, Central Maluku Regency - Kilmanun, Chrishard Leonardo; Siwalette, Jeter Donald; Kaplale , Raihana (Devotion : Journal of Research and Community Service, 2025)
Analysis of the Utilization of Village Funds in Community Empowerment in Haruru Village, Amahai District, Central Maluku Regency. Supervised by Jeter Donald Siwalette and Raihana Kaplale. This study aims to analyze the process of utilizing Village Funds and the factors influencing their use in community empowerment in Haruru Village. Using the purposive sampling method, the study found that the village government has implemented the principles of transparency and participation in the planning and management of Village Fund allocations.